2007
DOI: 10.1007/s11250-007-9018-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementing a high-protein ram press sunflower cake concentrate on smallholder milk production in Zimbabwe

Abstract: Ram press sunflower cake protein concentrate was formulated locally and its effect on the performance of dairy cows was compared with that of a commercial dairy concentrate. The effects of concentrate on roughage dry matter intake, milk yield and milk composition, live weight and calving intervals were similar for all concentrates, which indicated that the home grown dairy concentrates were as effective as the dairy commercial concentrate. The lack of significant differences in the concentrations of rumen NH3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…Such widespread failures resulted in large economic losses for small producers. Indeed, different studies have reported that improved livestock have high maintenance needs for weak production in extensive systems (Ngonogoni et al 2007). Also, under such conditions, improved breeds are less liable to survive and indigenous breeds are revealed to be more productive (Madalena et al 2002;Karugia et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Such widespread failures resulted in large economic losses for small producers. Indeed, different studies have reported that improved livestock have high maintenance needs for weak production in extensive systems (Ngonogoni et al 2007). Also, under such conditions, improved breeds are less liable to survive and indigenous breeds are revealed to be more productive (Madalena et al 2002;Karugia et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Shortage of and poor quality fodder have been reported to be two of the major limiting factors to smallholder dairy farming in the country (Ngongoni et al 2007). Mastitis is another major limiting factor; it is a disease of dairy cattle that causes low milk production and high economic losses (Ericsson-Unnerstad et al 2009;Tesfaye, Regasa & Kelay 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are no records, however, for the amount of milk produced in the smallholder sector, and its contribution to the household and national economies is largely unknown. Improvement of the smallholder dairy production is a possibility to increase food security and income for resource-poor farmers (Kabirizi et al 2004;Somda et al 2005;Ngongoni et al 2007a). …”
Section: Introductionmentioning
confidence: 99%